Comparative ultrasound study of gastric emptying between an isotonic solution and a nutritional supplement - Flora Margarida Barra Bisinotto; Luciano Alves Matias da Silveira; Tiago Caneu Rossi; Laura Bisinotto Martins; Gustavo Palis Zago; Mariana Andrade Lopes Mendonça (Revista Brasileira de Anestesiologia, 2019)
Abstract Background and objectives: Preoperative fasting may lead to undesirable effects in the surgical patient in whom there is a stimulus to ingesting clear liquids until 2 hours before anesthesia. The aim of this study was to evaluate the gastric emptying of two different solutions using ultrasound. Methods: In a prospective, randomized, blind study, 34 healthy volunteers ingested 200 mL of two solutions without residues in two steps: an isotonic solution with carbohydrates, electrolytes, osmolarity of 292 mOsm.L-1, and 36 kcal; and other nutritional supplementation with carbohydrates, proteins, electrolytes, osmolarity of 680 mO.L-1, and 300 kcal. After 2 hours, a gastric ultrasound was performed to assess the antrum area and gastric volume, and the relation of gastric volume to weight (vol.w-1), whose value above 1.5 mL.kg-1 was considered a risk for bronchoaspiration. A p-value <0.05 was considered statistically significant. Results: There was a significant difference between all parameters evaluated 2 hours after the ingestion of nutritional supplementation compared to fasting. The same occurred when the parameters between isotonic solution and nutritional supplementation were compared 2 hours after ingestion. Only one patient had vol.w-1 <1.5 mL.kg-1 2 hours after ingestion of nutritional supplementation; and only one had vol.w-1 >1.5 mL.kg-1 after ingestion of isotonic solution. Conclusion: This study demonstrated that gastric emptying of equal volumes of different solutions depends on their constitution. Those with high caloric and high osmolarity, and with proteins present, 2 hours after ingestion, increased the gastric volumes, which is compatible with the risk of gastric aspiration.